(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Pragmalinguistic theory cannot bypass functionalism either. If we do not approach the analysis of communicative activity from the point of view of the functional features of the linguistic system, it becomes a very difficult task to define pragmalinguistics and to determine the subject of its research. In this article, we have defined pragmalinguistics and provided information about several of its functions in the communication process.